Strategi Komunikasi Pemasaran Mini Soccer Relone Arena Dalam Membangun Brand Image - Ridho Yades; Ria Edlina (CV. ITTC INDONESIA, 2025)
This research aims to describe the marketing communication strategy used by Relone Arena, a mini soccer facility in Padang City, in building Brand Image through social media, especially Instagram Relone Arena faces a number of problems, including the failure to consistently achieve its target of 200 hours of field rental per month, low brand awareness among the public, and inconsistency in promotional content on Instagram in terms of both frequency and visual quality. Based on the We Are Social report (2024), Instagram is included in the top five most used social media in Indonesia, making it a potential platform in reaching target audiences, especially the younger generation. This research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results showed that Relone Arena has implemented eight integrated marketing communication strategies, namely advertising, sales promotion, event organization, public relations, direct marketing, interactive marketing, word of mouth, and personal selling. These strategies succeeded in forming a positive Brand Image as a premium sports venue and friendly service. However, the utilization of Instagram features such as paid advertisements and live broadcasts still needs to be improved to maximally expand audience reach.